PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING DALAM PEMBELAJARAN BILINGUAL TERHADAP HASIL BELAJAR TEMATIK SISWA KELAS V - Noge, Maria Desidaria; Oli, Yohanes Mite; Wau, Maria Patrisia (Universitas Nusantara PGRI Kediri, 2022)
This research aimed at finding out the effect of cooperative learning models of Student Facilitator and Explaining in Bilingual learning of the thematic learning achievement of class V in the group VI district of Boawae District Nagekeo. This research was experimental research using the research design of pseudo experiments, with the research draft